Pregnancy with complete heart block. Issue 1 (20th January 2022) - Swain, Sasmita; Routray, Satyanarayan; Behera, Sandhyarani; Mohanty, Swayamsiddha
Abstract : Pregnancy with complete heart block is rare, its management is not streamlined and requires a multidisciplinary team approach involving the obstetrician, cardiologist, anaesthesiologist and neonatologist. High index of suspicion in a woman with slow heart rate and electrocardiographic examination will ensure the diagnosis of this condition. Such patient can be managed conservatively or may require temporary or permanent pacemaker implantation. We present a 26-year-old primigravida with complete heart block at term pregnancy. She was asymptomatic throughout her pregnancy with pulse rate between 50 and 60 beats per minute. Vaginal delivery was planned under continuous ECG monitoring. Isoprenaline drip and temporary pacemaker were kept stand-by. However, for obstetric reasons caesarean section was performed successfully under spinal anaesthesia without a pacemaker. Method of anaesthesia was planned to keep the haemodynamics stable and drugs causing bradycardia were avoided.